2012
DOI: 10.1016/j.jhydrol.2011.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the water balance of the Upper Rhine Graben hydrosystem

Abstract: 16The Upper Rhine alluvial aquifer is an important transboundary water resource. However, as 17 in many alluvial systems, the aquifer inflows and outflows are not precisely known, due to the 18 difficulty in estimating the river infiltration flux and the boundary subsurface flow. To 19 provide a thorough representation of the aquifer system, a coupled surface-subsurface model 20 was applied on the whole aquifer basin, and several parameter sets were tested to investigate 21 the uncertainty due to poorly known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…They are often developed by national -Zhangye basin, China, 9,097 km 2 (Tian et al, 2015) (Wilcox et al, 2007) MODCOU / EauDyssée Saleh et al (2011) Pryet et al (2014) ? SAM model (Ledoux et al, 1989;Ledoux et al, 1984) RAPID, 1D Muskingum scheme (David et al, 2011) 1D Stream network hydraulic modelling HEC-RAS (Saleh et al, 2011) Conceptual model soil water-budget (Pryet et al, 2014) -Seine basin, France, 95,600 km 2 (Ledoux et al, 2007) -Rhône basin, 86,500 km 2 (Etchevers et al, 2001) -Upper Rhine basin, 13,900 km 2 (Thierion et al, 2012) -Somme basin, 6,433 km 2 (Habets et al, 2010;Korkmaz et al, 2009) (2000) Kim et al (2008) ? MODFLOW (river package) SWAT (Arnold et al, 1993;Arnold and Fohrer, 2005) Not represented (Sophocleous et al, 1999) Musimcheon Basin, South Korea, 198 km 2 (Kim et al, 2008) WaSiM, WaSiM-ETH Krause and…”
Section: Other Applications Of Loosely Coupled Schemes With Applicatimentioning
confidence: 99%
“…They are often developed by national -Zhangye basin, China, 9,097 km 2 (Tian et al, 2015) (Wilcox et al, 2007) MODCOU / EauDyssée Saleh et al (2011) Pryet et al (2014) ? SAM model (Ledoux et al, 1989;Ledoux et al, 1984) RAPID, 1D Muskingum scheme (David et al, 2011) 1D Stream network hydraulic modelling HEC-RAS (Saleh et al, 2011) Conceptual model soil water-budget (Pryet et al, 2014) -Seine basin, France, 95,600 km 2 (Ledoux et al, 2007) -Rhône basin, 86,500 km 2 (Etchevers et al, 2001) -Upper Rhine basin, 13,900 km 2 (Thierion et al, 2012) -Somme basin, 6,433 km 2 (Habets et al, 2010;Korkmaz et al, 2009) (2000) Kim et al (2008) ? MODFLOW (river package) SWAT (Arnold et al, 1993;Arnold and Fohrer, 2005) Not represented (Sophocleous et al, 1999) Musimcheon Basin, South Korea, 198 km 2 (Kim et al, 2008) WaSiM, WaSiM-ETH Krause and…”
Section: Other Applications Of Loosely Coupled Schemes With Applicatimentioning
confidence: 99%
“…Former applications used a fixed water level throughout the simulation period (Arnold et al, 1999;Chung et al, 2010;Flipo et al, 2007b;Gomez et al, 2003;Ke, 2014;Kim et al, 2008;Monteil, 2011;Perkins and Sophocleous, 1999;Ramireddygari et al, 2000;Thierion et al, 2012). Saleh et al (2011) showed that this methodology not only leads to biased assessments of streamaquifer exchanges, but also to biased estimates of the nearriver piezometric head distributions.…”
Section: The Conductance Model At the Regional Scalementioning
confidence: 99%
“…As the SAFRAN reanalysis is performed on so-called "symposium zones", assumed to be homogeneous in terms of climate characteristics, overestimation of rainfall is also possible if those zones are inaccurately delineated, as is probably the case for the Thines at Gournier bridge (#3) catchment. Some authors tried to overcome the rainfall underestimation problem in mountainous areas by interpolating the SAFRAN data across altitude bands (Etchevers et al, 2001;Lafaysse et al, 2011;Thierion et al, 2012), but these data were not available for the present study. In addition, SAFRAN re-analyses are based on existing rain gauges.…”
Section: Data Qualitymentioning
confidence: 99%